Optimalisasi Database dan Pembuatan Guidebook Layanan Sistem Informasi Desa Pupuan - Suyadnya, Nyoman Suta; Wijaya, I Nyoman Yudi Anggara; Utami, Nengah Widya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The rapid development of information technology has impacted the way people think and perceive various activities. This swift progress, along with its wide-ranging potential applications, opens up opportunities for quick access to and dissemination of information. In village governance, information technology is used to quickly disseminate information and provide village services. The village of Pupuan has implemented the OpenSID village information system. However, it is not yet fully utilized by the village staff because the data on the website has not been fully entered. Additionally, there are no guidelines for submitting requests on the village website. Based on this situation, the researcher conducted activities such as optimizing the village website database, creating articles on the village website, and creating user manuals and instructional videos for the website's services. These activities are expected to provide the benefits of a village information system to the government of Pupuan Village and the local community. As a result, the OpenSID website of Pupuan Village was successfully managed and developed through these activities, and the village staff gained a better understanding of the website's services through the provided training and user manuals.